Male–female sensitivity in climate-induced income insecurity: some empirical evidence from farming households in Northern Cameroon. Issue 8 (17th November 2021) - Molua, Ernest L.; Ayuk, Justine E.
ABSTRACT: African women's particular responsibilities in the family make them vulnerable to environmental change, exacerbated by the impacts of climate variability. In light of varying climatic conditions, this paper compares the exposure of female-headed and male-headed rural households to income risk induced by climate variation. Three hundred and twenty households and their farms are observed in the three Northern provinces of Cameroon. Most of them are livestock and crop farmers in a region characterised by high average daily temperatures, longer dry seasons, and shorter rainy seasons. The econometric assessment of incomes and market food expenditure (non-own farm-related expenses) indicates that increases in climate variability have an explicit impact on the expected farm and household incomes and expenditures on food, with significant implications for system's resilience and food security. Risk measured as variations in rainfall or temperature has an unexpected positive significant impact on incomes, with the impact more substantial in female-headed households. However, when the variations in rainfall and temperature double, households experience negative returns to income levels, indicating the insufficiency of the coping choices in cushioning the households against stronger shocks. This has significant consequences on household livelihood security.